2007
DOI: 10.1128/jvi.02010-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Pathobiology Studied in Humanized BALB/c-Rag2 −/− γ c −/− Mice

Abstract: The specificity of human immunodeficiency virus type 1 (HIV-1) for human cells precludes virus infection in most mammalian species and limits the utility of small animal models for studies of disease pathogenesis, therapy, and vaccine development. One way to overcome this limitation is by human cell xenotransplantation in immune-deficient mice. However, this has proved inadequate, as engraftment of human immune cells is limited (both functionally and quantitatively) following transplantation of mature human ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 32 publications
8
141
2
1
Order By: Relevance
“…Macrophage depletion using chemicals 34 or antibodies 35 may further enhance repopulation by human cells. It is also possible that the background strain of the mice (C57/BL6) is sub-optimal for xenorepopulation 17 . Although further improvements of the FRG model are likely, we have demonstrated here that human hepatocytes expanded in this system are useful for common drug metabolism studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage depletion using chemicals 34 or antibodies 35 may further enhance repopulation by human cells. It is also possible that the background strain of the mice (C57/BL6) is sub-optimal for xenorepopulation 17 . Although further improvements of the FRG model are likely, we have demonstrated here that human hepatocytes expanded in this system are useful for common drug metabolism studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rag2 −/− /Il2rg −/− mice have been reported to be excellent recipients of human hematopoietic xenografts 16,17 . Therefore the Fah mutation was crossed into this background, resulting in Fah/Rag2/Il2rg (FRG) triple mutants.…”
Section: Generation Of Fah −/− /Rag2 −/− /Il2rg −/− (Frg) Micementioning
confidence: 99%
“…VIH, virus du syndrome de l'immunodéficience acquise Un des premiers virus étudiés dans ce modèle de souris humanisées est le VIH, lentivirus à la fois lymphotrope et monocytotrope [19]. L'infection des souris BRG par ce virus reproduit chez ces souris des aspects spéci-fiques de la maladie, par exemple la déplétion des lymphocytes T CD4 + , la virémie et la dissémination du virus dans les organes lymphoïdes [20][21][22]. Cependant, la réponse des cellules B anti-VIH restant très faible dans ce modèle, les études se sont principalement focalisées, chez ces souris humanisées, sur les phases pré-coces de l'infection, notamment sur la transmission du virus au niveau des muqueuses vaginale et rectale.…”
Section: De L'immunodéficience à L'humanisation Un Grand Choix De Souunclassified
“…For example, within the SCID strain, the SCID with the NOD background was the gold standard for the xenotransplantation assay based on its high efficiency. 11 In fact, recent studies have shown that among the lymphoid-depleted mouse strains, the NOD-scid Il2rg null (NSG/NOG) 14,15 and NOD.Rag1 null Il2rg null (NOD-RG) 20 strains are the most efficient; the BALB/c.Rag2 null Il2rg null (BALB-RG) strain is the next efficient 21,22 ; and the C57BL/6 strains with scid, 23 Rag2 null , Rag2 null B2m null , Rag2 null Prf null , 24 or Rag2 null Jak3 null25 mutations are unable to reconstitute human hematopoiesis. The NOD strain has multiple immune deficiencies, including defects of appropriate regulation of the T-lymphocyte repertoire, antigen presenting cell function, NK cell function, 26 and hemolytic complement (C5) and cytokine production from macrophages, 27 and these abnormalities are presumed to collaborate to cause the development of autoimmune diabetes and hemolytic anemia.…”
Section: Introductionmentioning
confidence: 99%